The Effect of Outsourcing on Business Operations - Henry Odigie Isaiah; Asunmo Olakunle Olayide (Communications of International Proceedings, 2023)
Outsourcing has become a strategic business tool that has a relevant impact on how modern businesses operate. By examining the nuances of outsourcing strategies, organizations can make well-informed decisions that support their objectives and enhance their performance. This study aims to analyze the impact of onshore and offshore outsourcing on corporate operations. Analyzing the relationship between outsourcing and firm performance, this study aims to fill the research gap in literature by providing a thorough analysis of the impact of both onshore and offshore outsourcing on corporate operations. The data was analyzed using the regression technique with the aid of Special Package for Social Science (SPSS). This study contributes to knowledge by offering a comprehensive understanding of the intricate effects of both onshore and offshore outsourcing on corporate operations. The result study reveals that offshore and onshore outsourcing strategies have a substantial impact on operational capabilities. As a result, the study recommended that management should employ onshore and offshore outsourcing strategy is used in order to improve the operational capability of their organization.
Keywords: outsourcing; offshoring; onshoring; capabilities; strategy